Cerebellar activation during a motor task in conversion disorder with motor paralysis: A case report and fMRI study - Takamitsu Shimada; Kazutaka Ohi; Toshiki Yasuyama; Takashi Uehara; Yasuhiro Kawasaki (Wiley, 2018)
Abstract Background Motor conversion disorders are characterized by movement symptoms without a neurological cause. A psychogenic etiology is presumed for these disorders, but little is known about their underlying neural mechanisms. Functional magnetic resonance imaging (fMRI) has been utilized to understand the mechanisms associated with unexplained motor symptoms. Here, we used fMRI to investigate the cerebral response to motor stimulation in a patient with conversion disorder with motor paralysis to determine the underlying neural mechanisms of this disorder. Methods Brain activation induced by movements of the bilateral ankle joints (repeated plantar flexion and dorsiflexion) was recorded using fMRI in a patient with conversion disorder with unexplained motor paralysis. We acquired 2 types of imaging data: (i) data obtained while motor paralysis remained present and (ii) data obtained after motor paralysis had completely improved. We used a within‐subject fMRI block design to compare the patient's brain activities during the motor task and at rest. Results Cerebral motor areas were significantly activated during the motor task relative to at rest, both when motor paralysis remained present and when paralysis had improved (FWE‐corrected P < .05), although there was greater activation in motor areas when motor paralysis had improved than when motor paralysis remained. Notably, activation in the cerebellum posterior lobe during the motor task when motor paralysis remained (FWE‐corrected P < .05) disappeared after motor paralysis had completely improved. Conclusions The cerebellum is a region that is closely associated with voluntary motion. We suggest that complementary abnormal function in the cerebellum might be associated with the neural basis of conversion disorder with motor paralysis.